A critical appraisal on financial consumer protection in Malaysia - Ilias, Ibtisam@Ilyana; Amin, Naemah (2015)

(untitled)
Recently, the protection of financial consumer becomes a rising concern of many countries in this world. In Malaysia, Consumer Protection Act 1999 (CPA) is a present law aims at providing protection to general consumer including financial consumer. The coming into force of Financial Services Act 2013(FSA) and Islamic Financial Services Act 2013(IFSA) marks an important milestone in strengthening financial consumer protection and indicates a significant transformation in the legal framework vis-à-vis the protection and empowerment of this group of consumer. While the regulator accountable for consumer protection under FSA and IFSA is Bank Negara Malaysia (BNM), CPA is under the jurisdiction of Ministry of Domestic Trade, Cooperative and Consumerism (MDTCC). For that reason, this paper attempts to critically appraise key provisions under these three statutes with reference to financial consumer protection.